A Quantum-Classical Hybrid Classifier Using Multi-Encoding Method for Images - Bar, Niyazi Furkan; Yetis, Hasan; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2023)
Image data grows in volume and size more quickly than classical processing power. Thanks to its entanglement and super-position qualities, quantum computing, which is based on quantum physics, has a lot of potential for speed and processing capacity. For high power challenges, it is therefore highly common to try to utilize quantum computing units rather than classical computing units. In this study, a hybrid quantum-classical approach was proposed for utilizing quantum computers' advantages in image classification. This hybrid technique uses a variational quantum circuit (VQC) on the quantum computer side. To overcome the qubit restriction in the VQC, multiple amplitude encoding was used as the data encoding method. In the classical computer part of the proposed approach, the preprocessing of the image, the convolution operation, and the optimization of the parameters of the single-qubit rotation gates in the VQC were performed. The proposed approach was trained and tested on two different data sets. The accuracy rates acquired in 2-layers and 4-layers VQCs within the data sets were evaluated in the test results. The proposed approach was evaluated against studies that were similar in the literature. Compared to similar studies, it was observed that it is more successful in terms of the number of parameters used and quantum cost. As a result, the effectiveness of the proposed approach was verified. © 2023 IEEE.
27th International Conference on Information Technology, IT 2023 -- 15 February 2023 through 18 February 2023 -- Zabljak -- 187585
Keywords: image classifier; quantum computing; quantum machine learning; variational quantum circuit